Educaţia ecologică – între necesitate şi oportunitate - Öllerer, Kinga (Calitatea Vieții, 2012)
Ecological education, like the basic education from which it derives, is a field experiencing continuous transformation, requiring on-going clarification. Its main aim is to help people to acquire knowledge, think about environmental issues, and have direct experiences in the natural environment. This knowledge implies more than an accumulation of information, it has to contribute to the understanding and the capacity of evaluating information, leading to informed decision making. While formal education is basically provided by educational institutions, ecological education is mainly a responsibility undertaken by the civil society, even since its appearance. The advantage is that these entities have a strong connection with communities, based on informal relationships, in contrast with the educational institutions, which are centrally governed. This creates the opportunity to address the identity-link of local inhabitants, facilitating community involvement and the willingness to shift attitudes. The negative side is that, often, these programmes lack scientific accuracy, leading, in the end, to misinformation and environmental misconceptions. The present paper is a review of the history of development, it presents knowledge and major international initiatives in the field of environmental education, describing the case of Ţara Haţegului–Retezat region in Romania, which benefited from several projects in this sense.